Pretraining Experience and Structure of Surgical Training at a Sub-Saharan African University - Galukande, Moses; Ozgediz, Doruk; Elobu, Emmanuel; Kaggwa, Sam (World journal of surgery, 2013)
The common goal of surgical training is to provide effective, well-rounded surgeons who are capable of providing a safe and competent service that is relevant to the society within which they work. In recent years, the surgical workforce crisis has gained greater attention as a component of the global human resources in health problems in low- and middle-income countries. The purpose of this study was to: (1) describe the models for specialist surgical training in Uganda; (2) evaluate the pretraining experience of surgical trainees; (3) explore training models in the United States and Canada and areas of possible further inquiry and intervention for capacity-building efforts in surgery and perioperative care. Methods This was a cross-sectional descriptive study conducted at Makerere University, College of Health Sciences during 2011–2012. Participants were current and recently graduated surgical residents. Data were collected using a pretested structured questionnaire and were entered and analyzed using an excel Microsoft spread sheet. The Makerere University, College of Health Sciences Institutional Review Board approved the study.
Keywords: Pretraining Experience; Surgical Training; Sub-Saharan African University